The impact of cost of poor quality on continuous improvement initiatives : A case study on General Electric (Global Business Management Review (GBMR), 2025)
This study examines the impact of the Cost of Poor Quality (COPQ) on Continuous Improvement (CI) initiatives within General Electric (GE), addressing a critical gap in understanding how quality-related costs influence operational efficiency and financial performance. The study is motivated by the persistent challenge organizations face in mitigating COPQ while sustaining CI efforts. Utilizing Smart PLS 4.0, a two-step approach was employed, comprising measurement and structural modeling. The measurement model confirmed construct reliability and validity, while the structural model established significant relationships among key variables. The findings reveal that COPQ substantially undermines CI efficacy, leading to increased inefficiencies and reduced financial performance. Conversely, strategic investments in quality enhancement mitigate these costs and improve productivity and employee engagement. The study surveyed professionals across GE, achieving a response rate of 78.5%, with a majority of respondents aged 36 to 45 (49.1%) and possessing at least a bachelor's degree (46.9%). The results emphasize the necessity of a holistic approach to quality management, integrating COPQ considerations into CI strategies to optimize organizational performance. By elucidating these interactions, this research contributes to the broader discourse on quality management and CI, offering valuable insights for academia and industry. Simultaneously, the study's findings provide a foundation for future research and practical applications in diverse organizational contexts, reinforcing the need for proactive quality management strategies to enhance operational excellence.